Factors Contributing to Different Agency in Work and Study: A View on the "Forgotten Half". (December 2013) - Seiffge-Krenke, Inge; Persike, Malte; Luyckx, Koen
Most young adults today are following longer educational tracks and postpone entrance into the workforce. This 2-year study aimed to determine factors contributing to occupational self-efficacy in a representative sample of n = 1, 891 young adults ( M = 23.92, SD = 2.17 years) with different work statuses (studying, in an apprenticeship, employed, or unemployed). Occupational identity, perceived work quality, the ability to cope with work stress, and symptomatology were assessed. Path analyses revealed that work status was the most important predictor of later occupational self-efficacy, with employment showing the strongest prediction of later agency in the professional domain. Ruminative exploration, work stress, and internalizing symptoms contributed negatively to occupational self-efficacy, whereas commitment making and coping competence contributed positively to later agency in work and study. The discussion focuses on the early developmental roots of occupational self-efficacy.